WhpR, an orphan transcriptional regulator of virulence in the pathogen of woody hosts Pseudomonas savastanoi pv. savastanoi - Arroyo Mateo, Antonio; Leal López, Jesús; Ramos-Rodríguez, Cayo Juan (My University, 2022)
The genome of the olive tree pathogen Pseudomonas savastanoi pv. savastanoi (Psv) NCPPB 3335 encodes a region of about 15 kb named WHOP (from Woody Host and Pseudomonas) which is involved in the catabolism of aromatic compounds and is essential for the virulence of Psv in woody olive plants. This region is shared with other strains of Pseudomonas syringae pathovars infecting woody hosts, but it is absent in strains infecting herbaceous plants. The WHOP region is organized into four operons, antABC (metabolism of anthranilate), catBCA (catabolism of catechol) ipoBCA (oxigenase activity) and dhoAB (degradation of fenolic compounds) and three independently transcribed genes, antR (positive regulator of the antABC operon), PSA3335_3206 (aerotaxis receptor) and whpR (putative AraC family regulator). In this study we identified two domains in WhpR, a DBD (DNA bingding domain), characterised by a classical HTH (Helix-Turn-Helix) motif and an AraC-like bingding domain. BlastP searches showed that no homologs (≥ 60%) of this protein are found outside the P. syringae complex. We also addressed the role of WhpR in virulence by the construction of ΔwhpR mutants in several P. savastanoi strains isolated from olive and oleander (P. savastanoi pv. nerii). Moreover, quantitative real-time PCR (RT-qPCR) analysis of Psv NCPPB 3335 and its ΔwhpR mutant revealed that WhpR is a negative regulator of most of the operons encoded in the WHOP region. Our future aims are to elucidate the mechanism of WhpR-dependent regulation and to determine whether other genes codified outside the WHOP region are also regulated by WhpR.
Keywords: Pseudomonas; Pseudomonas savastanoi; WHOP; aromatic; Regulation